The Essential Guide to 3D in Flash - Olsson, Richard; Bateman, Rob (Apress : Imprint: Apress, 2010)
If you are an ActionScript developer or designer and you would like to work with 3D in Flash, this book is for you. You will learn the core Flash 3D concepts, using the open source Away3D engine as a primary tool. Once you have mastered these skills, you will be able to realize the possibilities that the available Flash 3D engines, languages, and technologies have to offer you with Flash and 3D. Describes 3D concepts in theory and their implementation using Away3D Dives right in to show readers how to quickly create an interactive, animated 3D scene, and builds on that experience throughout the book Each chapter contains a number of tutorials that focus on one specific feature or group of features.